(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
A rapid and simple method for simultaneous determination of acetamiprid and its metabolite 6-chloronicotinic acid in sweet cherry samples has been developed. This residue analysis method is based on the reversed phase separation on C18 column with gradient elution. Analytes’ determination and quantification were performed by high performance liquid chromatography (HPLC) with diode-array detector and chromatograms were extracted at 230 nm. Extraction efficiency experiments demonstrated the ability of this method to extract neonicotinoids from sweet cherry samples. These insecticides were extracted with a mixture of acetonitril/0.1N ammonium-chloride (8/2, v/v). The average recoveries of acetamiprid and 6-chlornicotinic acid from sweet cherry samples were in the range of 95-101% and 73-83%, respectively, with the associated relative standard deviations (RSDs) <5%. Expanded measurement uncertainties for the analyzed compounds were 2.7 and 3.01%. The limit of quantification (LOQ) was 10 µg/kg and 30 µg/kg for acetamiprid and 6-chloronicotinic acid, respectively. Thus, the developed HPLC/DAD method can be considered a useful tool for sensitive and rapid determination of acetamiprid and 6-chloronicotinic acid. Hence, the method may find further application in the analysis of real sweet cherry samples contaminated with these insecticides at a ppb level.